The Cape Observatory at 200. Issue 5 (1st October 2020) - Glass, Ian
Abstract : Ian Glass explores the origins of telescopic observing in South Africa, 200 years ago Abstract: Ian Glass looks back at the origins of telescopic observing in South Africa, 200 years ago.